Combining low temperature fluorescence DNA-hybridization, immunostaining, and super-resolution localization microscopy for nano-structure analysis of ALU elements and their influence on chromatin structure - Krufczik, Matthias; Hildenbrand, Georg Lars; Hausmann, Michael (International journal of molecular sciences, 2017)
Immunostaining and fluorescence in situ hybridization (FISH) are well established methods for specific labelling of chromatin in the cell nucleus. COMBO-FISH (combinatorial oligonucleotide fluorescence in situ hybridization) is a FISH method using computer designed oligonucleotide probes specifically co-localizing at given target sites. In combination with super resolution microscopy which achieves spatial resolution far beyond the Abbe Limit, it allows new insights into the nano-scaled structure and organization of the chromatin of the nucleus. To avoid nano-structural changes of the chromatin, the COMBO-FISH labelling protocol was optimized omitting heat treatment for denaturation of the target. As an example, this protocol was applied to ALU elements—dispersed short stretches of DNA which appear in different kinds in large numbers in primate genomes. These ALU elements seem to be involved in gene regulation, genomic diversity, disease induction, DNA repair, etc. By computer search, we developed a unique COMBO-FISH probe which specifically binds to ALU consensus elements and combined this DNA-DNA labelling procedure with heterochromatin immunostainings in formaldehyde-fixed cell specimens. By localization microscopy, the chromatin network-like arrangements of ALU oligonucleotide repeats and heterochromatin antibody labelling sites were simultaneously visualized and quantified. This novel approach which simultaneously combines COMBO-FISH and immunostaining was applied to chromatin analysis on the nanoscale after low-linear-energy-transfer (LET) radiation exposure at different doses. Dose-correlated curves were obtained from the amount of ALU representing signals, and the chromatin re-arrangements during DNA repair after irradiation were quantitatively studied on the nano-scale. Beyond applications in radiation research, the labelling strategy of immunostaining and COMBO-FISH with localization microscopy will also offer new potentials for analyses of subcellular elements in combination with other specific chromatin targets.